Analysing 'Wh' echo questions: a typological perspective with special reference to Hungarian - Mycock, L (Debreceni Egyetemi Kiado, 2019)
The study of Hungarian has provided and continues to offer important insights into how different aspects of linguistic structure may interact. As a classic discourse-configurational language in which syntax and information structure are closely related, research on Hungarian such as Laczkó (2017) has revealed much about discourse functions and how these can be encoded in the syntax. An important thread running through this research is the study of ‘wh’-question formation, not least because ‘wh’-questions have played such a crucial part in the development of modern syntactic theory. In this paper, I turn to a type of ‘wh’-question which surprisingly has received relatively little attention: the ‘wh’ Echo Question, or ‘wh’-EQ. I provide what is, to the best of my knowledge, the first exploration of the relevant typological space, before presenting the first analysis of ‘wh’- EQs in the framework of Lexical-Functional Grammar (LFG), taking Hungarian as the major case-study language. In order to provide a full analysis of ‘wh’-EQs cross-linguistically, I develop a consistent representation of speech acts in the LFG framework. This new approach offers a way to represent information about speech acts that is crucial to the analysis of not only ‘wh’-EQs but also reporting constructions (quotation) more generally. In turn, this work opens the door to exploring issues relating to the representation of discourse structure and pragmatics more widely within the LFG framework.